2020
DOI: 10.1111/josh.12931
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of 2 Support Models for a Healthy School Initiative*

Abstract: BACKGROUND In school year (SY) 2014‐2015, 128 schools in 24 districts and 14 states were randomly assigned to receive either onsite or online support to implement a school‐based wellness program. The objective of this study was to assess the cost‐effectiveness (CE) of the 2 models of implementation support: onsite and online. METHODS We adapted the “ingredients method” for the CE analysis. Using expenditure data, we tabulated the costs of relevant expense categories and allocated the appropriate proportion to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…114 Thirty-eight studies evaluated interventions with the main components cutting across multiple intervention categories. 31,38,[52][53][54]60,61,[63][64][65][66][67][68]70,73,75,76,79,80,83,94,[99][100][101][102][107][108][109][110][111]123,125,130,131,134,137,139,140 All but three of these multi-category interventions involved behavioral components: Of the three that did not, one intervention targeted food standards across English schools, 83 while two others sought to change the school drinking water environment in the United States. 73,76 One study considered hypothetical scenarios of reduction in the prevalence of obesity, and no intervention was specified.…”
Section: Key Cost-effectiveness Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…114 Thirty-eight studies evaluated interventions with the main components cutting across multiple intervention categories. 31,38,[52][53][54]60,61,[63][64][65][66][67][68]70,73,75,76,79,80,83,94,[99][100][101][102][107][108][109][110][111]123,125,130,131,134,137,139,140 All but three of these multi-category interventions involved behavioral components: Of the three that did not, one intervention targeted food standards across English schools, 83 while two others sought to change the school drinking water environment in the United States. 73,76 One study considered hypothetical scenarios of reduction in the prevalence of obesity, and no intervention was specified.…”
Section: Key Cost-effectiveness Resultsmentioning
confidence: 99%
“…60,61,67,75,76,106,107,109,111,112,167 The economic evaluation of e-health interventions ("the use of information and communications technology in support of health and health-related fields" 184 ) and interventions with m-health (a subset of ehealth based on mobile wireless technologies 185 ) components at their core emerged only within the past 5 years. 47,48,79,113,114,133,142,171,177 The costing of these interventions reveals contemporary complexities attended by the omission of associated resource use and costs. One study excluded costs relating to research and development of a multicomponent m-health intervention, 133 while another study reported difficulties obtaining similar costs.…”
Section: Study Characteristics Across All Intervention Groupingsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, no broad conclusions regarding the value for money offered by implementation interventions applied to public health interventions were possible. Further economic evaluations of public health implementation interventions have emerged since this review [45][46][47][48][49][50]; however, the field of work remains small and studies are highly variable by topic, research design, setting and outcome measure(s). Cost evaluations of public health implementation interventions, especially via cost-effectiveness estimates, are needed to enhance understanding and ultimately to increase the uptake of evidence-based practices across settings [41,43,51,52].…”
Section: Introductionmentioning
confidence: 99%